2022
DOI: 10.3389/fgene.2022.1032572
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanism of fibrosis-related genes in patients with heart failure

Abstract: Background: Heart failure (HF) is a complex clinical syndrome characterized by the inability to match cardiac output with metabolic needs. Research on regulatory mechanism of fibrosis-related genes in patients with HF is very limited. In order to understand the mechanism of fibrosis in the development and progression of HF, fibrosis -related hub genes in HF are screened and verified.Methods: RNA sequencing data was obtained from the Gene Expression Omnibus (GEO) cohorts to identify differentially expressed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Activation of TLR4 leads to the progression of cardiac hypertrophy and tissue damage [92]. In accordance with this evidence, Tao et al found TLR4 to be a hub gene capable of discriminating between HF and healthy human cardiomyocytes [90]. This observation suggests that FOXC1, as a regulator of TLR4, may play a role in the fibrotic processes associated with the development of heart failure.…”
Section: Variations In Transcription Factor Activity Profilesmentioning
confidence: 82%
See 1 more Smart Citation
“…Activation of TLR4 leads to the progression of cardiac hypertrophy and tissue damage [92]. In accordance with this evidence, Tao et al found TLR4 to be a hub gene capable of discriminating between HF and healthy human cardiomyocytes [90]. This observation suggests that FOXC1, as a regulator of TLR4, may play a role in the fibrotic processes associated with the development of heart failure.…”
Section: Variations In Transcription Factor Activity Profilesmentioning
confidence: 82%
“…The role of this Transcription Factor in HF possibly relates to the myocardial fibrosis process, defined as the excessive deposition of extracellular matrix in the cardiac interstitium, proliferation of cardiac fibroblasts, tissue repair, and scar formation [89]. Heart failure is often coupled with cardiac remodeling, a process characterized by various pathological changes, chief amongst which is myocardial fibrosis [90].…”
Section: Variations In Transcription Factor Activity Profilesmentioning
confidence: 99%
“…In accordance with this evidence, Tao at al. found TLR4 to be a hub gene, capable of discriminating between HF and healthy human cardiomyocytes 72 . This observation suggests that FOXC1, as a regulator of TLR4, may play a role in the fibrotic processes associated with the development of heart failure.…”
Section: Variations In Transcription Factor Activity Profilesmentioning
confidence: 99%
“…The role of this Transcription Factor in HF possibly relates to the myocardial fibrosis process, defined as the excessive deposition of extracellular matrix in the cardiac interstitium, proliferation of cardiac fibroblasts, tissue repair, and scar formation 71 . Heart failure is often coupled with cardiac remodeling, a process characterized by various pathological changes, chief amongst which is myocardial fibrosis 72 .…”
Section: Variations In Transcription Factor Activity Profilesmentioning
confidence: 99%
“…The application of these techniques has become widespread in the exploration of disease pathogenesis and molecular mechanisms, deepening our comprehension and knowledge of disease. A bioinformatics analysis revealed that six genes were identi ed as diagnostic brosis-related genes (FRGs) in heart failure, suggesting that they may be novel biomarkers for the treatment of heart failure [10]. KLF2 is strongly associated with brosis in hepatocellular carcinoma, which might be an essential promoter of cancer progression [11].…”
Section: Introductionmentioning
confidence: 99%